HUBUNGAN SIZE DAN FUNGSI DENGAN KULTUR ORGANIZATIONAL PERUSAHAAN MANUFAKTUR DI INDONESIA - Nur Indriantoro (Journal of Indonesian Economy and Business (JIEB), 2000)
This study extends Pratt and Beaulieu (1992) to examine the differences in organizational culture of public companies due to various aspects of organizational culture: size, technology, rank, and various organizational functions. This study uses different concept of culture with the one used by Pratt and Beaulieu (1992). The concept of culture used in this study is the organizational culture developed by Hofstede et al. (1990) in their study on cross-cultural within cross-organizations. This study reveals that size does not relate with organizational culture. This study does not support previous research by Hofstede et al. (1990) and Pratt and Beaulieu (1992).